2013
DOI: 10.5187/jast.2013.55.3.185
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Characteristics and Probability of Individual Discrimination in Korean Indigenous Chicken Brands by Microsatellite Marker

Abstract: Microsatellite markers have been a useful genetic tool in determining diversity, relationships and individual discrimination studies of livestock. The level of genetic diversity, relationships among two Korean indigenous chicken brand populations (Woorimatdag: WR, Hanhyup3: HH) as well as two pure populations (White Leghorn: WL, Rhode Island Red: RIR) were analyzed, based on 26 MS markers. A total of 191 distinct alleles were observed across the four chicken populations, and 47 (24.6%) of these alleles were un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…On the other hand, close genetic distances of the WM1 population with the CoL, Hh, and RIR populations (0.1375, 0.2453, and 0.2478, respectively) were observed. These results support the findings by Suh et al [ 25 ] that the WM1 and Hh populations have the same founder breeds as their genetic distances are close (Table 3 ). The WM2 population, however, has a genetic distance >0.690 indicating that different crossing combinations were applied between the WM2 and WM1 populations.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…On the other hand, close genetic distances of the WM1 population with the CoL, Hh, and RIR populations (0.1375, 0.2453, and 0.2478, respectively) were observed. These results support the findings by Suh et al [ 25 ] that the WM1 and Hh populations have the same founder breeds as their genetic distances are close (Table 3 ). The WM2 population, however, has a genetic distance >0.690 indicating that different crossing combinations were applied between the WM2 and WM1 populations.…”
Section: Resultssupporting
confidence: 91%
“…This indicated that the WM1 and Hh populations originated from the same breed/ancestor for constructing the populations. Furthermore, according to the genetic distance values, our marker combination has a stronger discriminating power than that in the findings by Suh et al [ 25 ]. On the other hand, close genetic distances of the WM1 population with the CoL, Hh, and RIR populations (0.1375, 0.2453, and 0.2478, respectively) were observed.…”
Section: Resultsmentioning
confidence: 48%
See 3 more Smart Citations